HIV diagnosis in Equatorial Guinea. Keys to reduce the diagnostic and therapeutic delay - Ana Rodríguez-Galet; Judit Ventosa-Cubillo; Verónica Bendomo; Manuel Eyene; Teresa Mikue-Owono; Jesús Nzang; Policarpo Ncogo; Agustín Benito; África Holguín (Elsevier, 2024)
Background: In Equatorial Guinea, only 54 % of people living with HIV know their HIV status. There are no confirmatory or molecular diagnostic techniques for early diagnosis or monitoring of infection in the country. Rapid diagnostic tests can induce false-positive diagnoses if used as a confirmatory technique. Our study aimed to identify the challenges of early HIV diagnosis in Equatorial Guinea by analyzing the rate of false positive diagnoses, diagnostic and therapeutic delays, and treatment failures among those on antiretroviral therapy. Methods: From 2019-2022, dried blood from 341 children, adolescents and adults diagnosed in Equatorial Guinea as HIV-positive by rapid diagnostic testing, and from 54 HIV-exposed infants were collected in Bata and sent to Madrid to confirm HIV-infection by molecular (Xpert HIV-1Qual, Cepheid) and/or serological confirmatory assays (Geenius-HIV-1/2, BioRad). HIV diagnostic delay (CD4 <350cells/mm3), advanced disease at diagnosis (CD4 <200cells/mm3) and antiretroviral treatment delay and failure (viraemia >1,000RNA-HIV-1-copies/ml) were also studied after viral quantification (XpertVL HIV-1, Cepheid). Results: False-positive diagnoses were identified in 5 % of analysed samples. HIV infection was confirmed in 90.5 % of previously diagnosed patients in Equatorial Guinea and 3.7 % of HIV-exposed children undiagnosed in the field. Two-thirds of each new HIV patient had delayed diagnosis, and one-third had advanced disease. Treatment delay occurred in 28.3 % of patients, being around four times more likely in adolescents/adults than children. More than half (56 %) of 232 treated patients presented treatment failure, being significantly higher in children/adolescents than in adults (82.9 %/90 % vs. 45.6 %, p < 0.001). Conclusion: We identified some challenges of early HIV diagnosis in Equatorial Guinea, revealing a high rate of false positive diagnoses, diagnostic/treatment delays, and treatment failures that need to be addressed. The implementation of more accurate rapid diagnostic techniques and confirmatory tests, along with improving access to care, treatment, awareness, and screening, would contribute to controlling the spread of HIV in the country.